Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Bagian Pelinting di KSU Perdula Ngoro Jombang) - Agus Huda Muhson; Mahfudiyanto Mahfudiyanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the effect of job satisfaction and job stress on employee performance (a case study in the pelinting section of the ngoro jombang first session). The method used in this study is a quantitative research method and uses an associative analysis approach. The results of the study show that: (1) Job satisfaction has a partial and simultaneous influence on employee performance in KSU Perdula Ngoro Jombang, meaning that if job satisfaction increases, employee performance will also increase or vice versa, if job satisfaction decreases, employee performance will also decrease. (2) Job stress has no effect partially on the performance of KSU Perdula Ngoro Jombang employees, meaning that job stress has no effect on improving employee performance. (3) Job satisfaction and job stress have a joint (simultaneous) effect on the performance of KSU Perdula Ngoro Jombang employees, meaning job satisfaction and job stress together to give n contribution in improving the performance of KSU Perdula Ngoro Jombang employees. So, if job satisfaction and job stress increase, the performance of KSU Perdula employees will also increase, conversely if if job satisfaction and job stress decrease, the performance of KSU Perdula employees will also decrease.